(untitled) (LEARNing Landscapes, 2016)
In this interview, Sara Lawrence-Lightfoot describes the genesis of the portraiture methodology and how it has developed over the past three decades. Portraiture seeks to blend art and science, bridging empiricism and aestheticism. It draws from a wide variety of phenomenological and narrative traditions. One of the ways in which it is distinct from other research methodologies is in its focus on "goodness"; documenting what is strong, resilient, and worthy in a given situation, resisting the more typical social science preoccupation with weakness and pathology. Dr Lawrence-Lightfoot also explains the work she does with her students at Harvard and gives examples of their research projects. She nishes by giving words of advice to those researchers interested in using the portraiture methodology.